2008
DOI: 10.1016/j.jcmg.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Subendocardial Ischemia in the Left Anterior Descending Coronary Artery Territory With Real-Time Myocardial Contrast Echocardiography During Dobutamine Stress Echocardiography

Abstract: In patients with significant LAD disease, RTMCE during DSE detects subendocardial ischemia even when transmural WT appears normal. Real-time myocardial contrast echocardiography should be the preferred ultrasound imaging method when using contrast to detect coronary artery disease during DSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…RTMCE was performed using ultrasound scanners equipped with low mechanical index real-time pulse sequence schemes. [8][9][10][11][12][13] This utilized a mechanical index of <0.2, frame rates of 20 to 25 H, time gain compensation higher in the near field, focus at the mitral valve plane or below, and overall gain settings adjusted so that brief high mechanical index impulses uniformly clear the myocardial segments of any signals.…”
Section: Imaging Techniques With Ultrasound Contrastmentioning
confidence: 99%
See 1 more Smart Citation
“…RTMCE was performed using ultrasound scanners equipped with low mechanical index real-time pulse sequence schemes. [8][9][10][11][12][13] This utilized a mechanical index of <0.2, frame rates of 20 to 25 H, time gain compensation higher in the near field, focus at the mitral valve plane or below, and overall gain settings adjusted so that brief high mechanical index impulses uniformly clear the myocardial segments of any signals.…”
Section: Imaging Techniques With Ultrasound Contrastmentioning
confidence: 99%
“…Real-time myocardial contrast echocardiography (RTMCE) is a technique that utilizes ultrasound contrast for the simultaneous analysis of myocardial perfusion and wall motion (WM) during stress echocardiography. 7,8 This perfusion technique measures capillary blood flow (CBF) and volume, and thus can indirectly assess capillary microvascular resistance. 2,3 Previous studies have shown that the detection of CBF abnormalities identified with RTMCE during stress echocardiography improve the ability of echocardiography to predict patient outcome during both demand and vasodilator stress.…”
mentioning
confidence: 99%
“…In a study involving 50 patients, realtime myocardial perfusion with contrast was performed during DSE. Subendocardial perfusion abnormalities that corresponded to myocardial ischemia were observed in areas where wall thickening was still preserved (21) and could further enhance the accuracy of DSE for the detection of CAD (Fig. 3).…”
Section: Figure 2 Coronary Computed Tomography Angiography With Low mentioning
confidence: 97%
“…Reprinted, with permission, from Xie et al (33). (55). Because dobutamine will recruit the subepicardial layers to contract, these wall-thickening abnormalities would have gone undetected if contrast were only used to enhance endocardial borders.…”
Section: Figure 3 An Example Of a Subendocardial Perfusion Defectmentioning
confidence: 99%
“…If only transmural wall thickening were examined in this patient (Pre-MCR after High MI Impulse images), the wall thickening would have appeared normal. Reprinted, with permission, from Xie et al (55). MCR ϭ myocardial contrast replenishment.…”
Section: Figure 5 An Example Of a Subendocardial Wall-thickening Abnmentioning
confidence: 99%